Sistem Keamanan Untuk Otorisasi Pada Smart Home Menggunakan Pengenalan Wajah Dengan Library OpenCV - Moh Eki Riyadani; Subiyanto Subiyanto (Teknik Informatika, 2022)
As industrial 4.0 advances such as Internet of Things (IoT), Big Data, Cloud Computing , and Artificial Intelligent (AI) has prompted reseachers to innovate in various fields, including security systems. The security system is an important issue due to rise of theft in a residence. A security system is needed for home authorizon to prevent the crime of theft. Security systems are built using facial recognition. The research proposes to develop a security system using facial recognition based Raspberry Pi with Python programming and utilize the OpenCV. System testing includes training function testing, facial recognition function, image delevery function, decision-making function, and system performance testing, system performance for facial recognition is calculated using confusion matrix formula that produces 100% sensitivity, 13% specitificity, and 97% accuracy.